The Using of Laboratory Social Studies as a Learning Resources in Junior High School - Mentari, Neviratujuian (International Journal Pedagogy of Social Studies, 2021)
Nowadays many schools do not have a laboratory for Social Sciences, but the Social Sciences laboratory is considered to support the study of the eyes of Social Sciences well. The essence of the laboratory serves as a means where the activities develop and find out the truth of the material that one can from the interested. Any method used to examine this phenomenon is through a qualitative method with the descriptive approach. The steps of data retrieval include interviews with the deputy headmaster, teachers, and six learners. The analysis of data in this research is done by processing qualitative data expressed in the form of words. Results obtained from this research are that each speaker agreed to assert that the development of a Social Sciences laboratory should have been done because it is very helpful to improve the understanding and creativity of students in learning. With the conclusion based on data processing that the Social Sciences laboratory can be a model of development, learning resources that will be effective to improve the study of Social Sciences that are still monotonous and less-liked learners with the provision of facilities that can improve the quality of learners in learning.